Associations between Psychiatric Disorders and Cannabis-Related Disorders Documented in Electronic Health Records. Issue 3 (26th May 2020) - Campbell, Anne; Bailey, Steffani R.; Hoffman, Kim A.; Ponce-Terashima, Javier; Fankhauser, Katie; Marino, Miguel; McCarty, Dennis
ABSTRACT: Data from a large network of community health centers connected via a single electronic health record (EHR) system examined associations between psychiatric disorders and documentation of a cannabis-related disorder among patients with reported cannabis use. Participants were adults who had at least one ambulatory visit at a clinic in three states between 1/1/2012 and 12/31/2016 and had either 1) a documented cannabis-related disorder indicated by an ICD-9/10 code on the problem list or encounter list or 2) documentation of cannabis use in the EHR social history section. Clinics included 101, 405 patients with either cannabis use recorded in the social history of the EHR (n = 71, 660) or a cannabis-related disorder documented in the encounter or problem list (n = 29, 745). GEE logistic regression modeling estimated adjusted odds ratios (aOR). Odds of patients having cannabis-related disorder recorded on the encounter or problem list were higher for individuals with depression (aOR = 1.08, 95% CI: 1.04–1.13), anxiety (aOR = 1.16, CI: 1.11–1.21) and bipolar disorder (aOR = 1.16, CI: 1.10–1.23). A diagnosis of schizophrenia increased the odds of a cannabis-related disorder by 62% (aOR = 1.62, CI: 1.48– 1.78). Primary care providers should routinely screen for and document cannabis-related disorders and psychiatric disorders.